THUJA AND ITS FORMS IN PARKS AND GARDENS PLATING OF MAKHACHKALA - M. R. Khizrieva (Юг России: экология, развитие)
The formula of variety of genus Thuja and its use in landscape gardening is analysed. The shaped variety of Thuja and first of all forms of Thuja western gives ample opportunities of creation of various landscape gardening compositions.